2016
DOI: 10.5506/aphyspolb.47.509
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the J-PET Detector for Studies of Discrete Symmetries in Decays of Positronium Atom --- A Purely Leptonic System

Abstract: The Jagiellonian Positron Emission Tomograph (J-PET) was constructed as a prototype of the cost-effective scanner for the simultaneous metabolic imaging of the whole human body. Being optimized for the detection of photons from the electron-positron annihilation with high time-and high angular-resolution, it constitutes a multi-purpose detector providing new opportunities for studying the decays of positronium atoms.Positronium is the lightest purely leptonic object decaying into photons. As an atom bound by a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 108 publications
0
89
0
Order By: Relevance
“…J-PET detector has been already built [1]. The mechanical construction for the next phases J-PET+1 and J-PET+2 is also prepared and the hardware upgrade is planned within the next 2 yearsLayer numberLayer radius with respect to the center of scintillator (cm)Number of scintillators in the layerAngular displacement of scintillatorJ-PET   142.5048    246.7548    357.5096 J-PET+2   142.5048    246.7548    350.9096    453.3096    557.5096 J-PET+1   142.5048    246.7548    353.3096    457.5096 J-PET-full   143.0400    245.0437 ...…”
Section: Performance Assessment: Monte Carlo Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…J-PET detector has been already built [1]. The mechanical construction for the next phases J-PET+1 and J-PET+2 is also prepared and the hardware upgrade is planned within the next 2 yearsLayer numberLayer radius with respect to the center of scintillator (cm)Number of scintillators in the layerAngular displacement of scintillatorJ-PET   142.5048    246.7548    357.5096 J-PET+2   142.5048    246.7548    350.9096    453.3096    557.5096 J-PET+1   142.5048    246.7548    353.3096    457.5096 J-PET-full   143.0400    245.0437 ...…”
Section: Performance Assessment: Monte Carlo Simulationsmentioning
confidence: 99%
“…Therefore, it is well suited for the studies of these discrete symmetries in the leptonic sector. These symmetries may be studied by the measurement of the expectation values of various operators (odd with respect to the studied symmetry) constructed from the momenta of photons and the spin of the ortho-positronium [1]. Such studies are limited by the photon–photon interaction, however it was estimated that the vacuum polarisation effects may mimic the CP and CPT symmetries violation only at the level of 10 [2], which is still by six orders of magnitude less than the presently best known experimental limits for CP and CPT violations in the positronium decays which are at the level of 0.3 % [3, 4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This polarization is to large extent preserved during the thermalization process and transferred to the positronium [28,29]. How- The ability to reconstruct the o-Ps decay vertex allows for a different way of polarization estimation, presented schematically in Figure 4 [14]. If a β + source is located inside a vacuum-filled cylinder covered with a layer of a medium for positronium formation (such as aerogel), then reconstructed position of the o-Ps→ 3γ decay can be used to obtain the positron momentum direction.…”
Section: Advantages Of O-ps→ 3γ Decay Vertex Reconstructionmentioning
confidence: 99%
“…Detailed description of potential of the J-PET detector for studies of discrete symmetries in decays of positronium atom can be found in Ref. [14].…”
Section: Prospects Of Discrete Symmetry Studies With the J-pet Detectormentioning
confidence: 99%